PENERAPAN HYGIENE SANITASI DALAM PROSES PENGOLAHAN MAKANAN DI KITCHEN FOX HOTEL PEKANBARU PROVINSI RIAU - Niken Puspita; Andi Moh Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Hygiene is a preventive health effort that focuses its activities on individual health efforts, as well as human personal health efforts. The definition of sanitation is a health effort to protect and prevent disease that focuses its activities on human environmental health efforts. This study aims to determine the application of food processing sanitation hygiene and to determine the efforts of the management in implementing processing sanitation hygiene in the implementation of food sanitation at Fox Hotel Pekanbaru. In this study, the authors used qualitative methods as a procedure for processing data. The data collection techniques used were observation, interviews and documentation of FBM, Executive Chef, Chef De Partie, Demi Chef, Cook and Cook Helper Fox Hotel Pekanbaru. After conducting interviews with the informants, the authors concluded that overall sanitation Hygiene in Fox Hotel Pekanbaru's kitchen was going well, but there are 2 things about sanitation Hygiene that need more attention, namely the necessity of wearing gloves when preparing or processing food and paying attention to the cleanliness of materials. raw foods such as washing vegetables and fruits before entering the kitchen. Key words: Hygiene, sanitation, application, food processing, kitchen